Kinetic and Antimicrobial Studies on Some Novel Mixed Ligand Complexes of Thorium(IV) and Dioxouranium(VI) Ions - Rajendran, G.; Kala Kumari, C.R. (Asian Journal of Chemistry, 2016)
A new series of mixed ligand complexes of Th(IV) and UO2(VI) with a Schiff base derived from vanillin and p-anisidine (HMBAMB), dimethyl sulphoxide (DMSO) and various anions have been synthesized. These complexes were characterized by various physico-chemical data such as CHN, metal ion contents, spectral, magnetic and molar conductivities. The thermal stability along with the kinetic parameters were determined by mechanistic and non-mechanistic equations applicable to thermal decomposition studies. The mechanisms of different decomposition stages were proposed from the kinetic data. Antimicrobial activity of the ligand and the complexes against different bacteria was studied. From these experimental observations compositions of the complexes were ascertained to be [UO2(HMBAMB)4(DMSO)2a2)], [UO2(HMBAMB)4(DMSO)2(aa)], [Th(HMBAMB)4(DMSO)2(a)4] and [Th(HMBAMB)4(DMSO)2(aa)2] where HMBAMB is representing the ligand, 4N(4'-hydroxy-2'-methoxybenzalidene)aminomethoxy benzene, a = monovalent anions such as acetate, nitrate and thiocyanate and aa = divalent anion, viz., sulphate. In these complexes, the primary ligands, viz., schiff base and DMSO act as neutral monodentate and the coordinating anions viz., acetate, nitrate, thiocyanate as monodentate and the sulphate ion as bidentate.